Effect of Nitrogen and Boron on the Performance of Wheat (Journal of Environmental Science and Natural Resources, 2015)
A field experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh from November 2011 to March 2012 to find out the effect of nitrogen (N) and boron (B) fertilization on the performance of wheat. The experiment comprised of four levels of N viz., 0, 80, 120, 160 kg ha-1 and three levels of B viz., 0, 1 and 2 kg ha-1. The experiment showed that there were significant differences in yield due to the application of N and B though some of the yield attributes were not found significant. Grain yield was found to be significantly and positively correlated with number of effective tillers plant-1, number of fertile spikelets spike-1, number of gains spike-1 and straw yield. A result showed that grain yield of wheat was increased with increasing levels of both N and B up to 120 kg ha-1 and 2 kg ha-1, respectively. The interaction effect of N and B on both the parameters was significant.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22154 J. Environ. Sci. & Natural Resources, 7(1): 105-110 2014